Dynamical Analysis and Control of a Chaotic Microelectromechanical Resonator Model - Bassinello, Dailhane G. [UNESP]; Tusset, Angelo M.; Rocha, Rodrigo T.; Balthazar, Jose M. [UNESP] (Hindawi Ltd, 2018)
The dynamic analysis and control of a nonlinear MEM resonator system are considered. Phase diagram, bifurcation diagram, and the 0-1 test are applied to the analysis of the influence of the parameters on the dynamics of the system, whose parameters are damping coefficient, polarization of the voltage, and nonlinear stiffness term. The bifurcation diagram is used to demonstrate the existence of the pull-in effect. Numerical results showed that the parameters, which were taken into account, were significant, indicating that the response can be either chaotic or periodic behavior. In order to bring the system from a chaotic state to a periodic orbit, two controls are considered: the time-delayed feedback control and the sliding mode control.